Chemical composition, antioxidant and antimicrobial activities of the essential oils from rhizomes and leaves of Alpinia conchigera Griff. (Zingiberaceae) - Qamaruz Zaman, Faridah; Ridzuan, Raihana; Abdelmageed, Adil Hassan Ahmed (Taylor and Francis, 2021)
This study was conducted to assess the potential of essential oils isolated from rhizomes and leaves of Alpinia conchigera as a source of bioactive compounds through the characterization of its chemical composition, antioxidant, and anti-microbial activities. Essential oils (EOs) from the leaves and rhizomes of this species were isolated using the hydrodistillation method. The chemical compositions of EOs were analyzed by using GC and GC-MS. The major compound of the rhizome EO was eucalyptol (60.58 %), whereas the most abundant compound in the leaf EO was β-bisabolene (46.70 %). The rhizome EO contained the most abundant polyphenolic compounds that possessed higher antioxidant activities compared to leaf EO and the reference antioxidant agent butylated hydroxytoluene (BHT). In addition, there exist a positive correlation between total phenolic content and antioxidant activities using DPPH (R2= 0.7634, p < 0.05) and β-carotene antioxidant activity (R2 = 0.6865, p < 0.05). Disc diffusion assay of the essential oils indicated that the rhizome oil possessed moderate inhibitory activity against all tested bacteria and fungi, whereas leaf EO inhibited only Gram-positive bacteria. The results indicated the potential of these EOs to exert beneficial antibacterial and antifungal effects and could serve as a promising natural cheap source of antioxidants that could be used in the food and pharmaceutical industries.